2023
DOI: 10.1128/aem.01603-22
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-Sensitive Comamonas thiooxidans Biosensor for the Rapid Detection of Enzymatic Polyethylene Terephthalate (PET) Degradation

Abstract: Plastics and microplastics accumulate in all ecological niches. The construction of more sensitive biosensors allows to monitor and screen potential PET degradation in natural environments and industrial samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…5 A). While Comamonas is commonly recognized as capable of degrading TPA (Dierkes Robert et al 2022 ; Hosaka et al 2013 ), the utilization of EG and BHET has not been characterized before. This means that CNB-1-based whole-cell biocatalyst can completely mineralize the PET microplastics, rather than merely degrading it into smaller molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A). While Comamonas is commonly recognized as capable of degrading TPA (Dierkes Robert et al 2022 ; Hosaka et al 2013 ), the utilization of EG and BHET has not been characterized before. This means that CNB-1-based whole-cell biocatalyst can completely mineralize the PET microplastics, rather than merely degrading it into smaller molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Comamonadaceae is a dominant species in the activated sludge system, comprising more than 2% of the total abundance of sludge microorganisms (Wu et al 2019 ; Zhang et al 2020a ). Additionally, studies have reported that Comamonas can degrade terephthalic acid (TPA) and ethylene glycol (EG), which are the main products of PET depolymerization (Aksu et al 2021 ; Dierkes Robert et al 2022 ; Hosaka et al 2013 ; Ma et al 2009 ). The objective of this study is to create a whole-cell biocatalyst for the degradation of PET microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…The species of the genus Comamonas are commonly found in a variety of environmental samples and are among the common bacteria in soil [5,6], food waste compost [7], wetlands [8] and wastewater treatment systems [9,10]. In addition, the genus Comamonas has a broad metabolic capacity to degrade various organic and inorganic substrates, including amino acids, aromatic compounds, carboxylic acids, heavy metals and steroids [11][12][13]. Moreover, several studies have extensively described the roles of Comamonas species in the processes of wastewater bioaugmentation and bioremediation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among emerging applications of genetically encoded biosensors, these tools are expected to play a significant role in advancing and supporting the biological synthesis and degradation of plastics, contributing to achieving greater waste circularity 2729 . For example, to support the transition away from petrochemical-based to renewable feedstocks, biosensors have been applied to facilitate metabolic engineering efforts to produce drop-in monomer precursors and/or for bio-based plastic production 4,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, to support the transition away from petrochemical-based to renewable feedstocks, biosensors have been applied to facilitate metabolic engineering efforts to produce drop-in monomer precursors and/or for bio-based plastic production 4,30,31 . Additionally, biosensors can be highly powerful screening tools to discovery and optimize novel enzymes for the efficient breakdown of plastics 27,28 . Here, we applied DoE as a design framework to achieve customised performance of activator-based biosensors.…”
Section: Introductionmentioning
confidence: 99%